Conceiving Family: A Practical Theology of Surrogacy and Self: by Danielle Tumminio Hansen, Waco, TX, Baylor University Press, 2019, 229 pp. (Hard cover), $39.95, ISBN: 978-1481310567. - Feske, Millicent (Journal of Pastoral Theology, 2023)
Tumminio Hansen argues that the ethical and theologically sound practice of surrogacy, though difficult to achieve in US culture with its marketplace mentality and conflicting regulations (or lack thereof) for making surrogacy arrangements, can become a source of redemption for all involved. Over the past 40 + years, a wealth of academic and popular literature has investigated and judged surrogacy as a means to overcome infertility and pregnancy. Conceiving Family: A Practical Theology of Surrogacy and Self: by Danielle Tumminio Hansen, Waco, TX, Baylor University Press, 2019, 229 pp.